Some Elements of Chris MacDonald’s Business Ethics - Sroka, Robert (Diametros, 2019)
The goal of the article is to make an attempt to describe the characteristic features of the systemic approach to business ethics of the Canadian philosopher Chris MacDonald. MacDonald’s views are presented against the background of the characteristic features of Canadian business ethics. The fundamental ethical categories that MacDonald uses are discussed, and an ethical analysis of the real challenges of business practice is provided. The material presented allows the methods used by MacDonald to be captured and his views on the important ethical dilemmas of business to be imparted.